Biodegradable magnesium fuel-based Janus micromotors with surfactant induced motion direction reversal; Colloids and Surfaces B: Biointerfaces; Vol. 218 - Zhao Zewei; Si Tieyan; Kozelskaya A. I. Anna Ivanovna; Akimchenko I. O. Igor Olegovich; Tverdokhlebov S. I. Sergei Ivanovich; Rutkowski S. Sven; Frueh J. С. Johannes Christoph (2022, 2022)
Title screen